2010
DOI: 10.1007/s00268-010-0602-5
|View full text |Cite
|
Sign up to set email alerts
|

Afferent Loop Obstruction After Distal Gastrectomy with Roux‐en‐Y Reconstruction

Abstract: Afferent loop obstruction develops rarely after distal gastrectomy with Roux-en-Y reconstruction through an open approach. This rare but fatal complication should be considered when a patient complains of abdominal pain and/or vomiting after distal gastrectomy with Roux-en-Y reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 21 publications
2
50
0
1
Order By: Relevance
“…Roux-en-Y anastomosis avoids anastomosis at the crossing site of the afferent and efferent loops and reduces such complications as afferent loop obstruction, so A-loop obstruction is very rarely following Roux-en-Y reconstruction [2]. In the radical resection of gastric carcinoma in this patient, Roux-en-Y anastomosis of radical gastrectomy was performed.…”
Section: Discussionmentioning
confidence: 88%
“…Roux-en-Y anastomosis avoids anastomosis at the crossing site of the afferent and efferent loops and reduces such complications as afferent loop obstruction, so A-loop obstruction is very rarely following Roux-en-Y reconstruction [2]. In the radical resection of gastric carcinoma in this patient, Roux-en-Y anastomosis of radical gastrectomy was performed.…”
Section: Discussionmentioning
confidence: 88%
“…A retrospective review of 1908 patients following gastrectomy with Roux-en-y reconstruction found that four patients (0.2%) went on to develop ALS, the causes being internal herniation in two, adhesion in one and peritoneal recurrence in the other. The period between initial and emergency operations had a median of 5 months [4].…”
Section: Discussionmentioning
confidence: 99%
“…ALS is a serious condition with an estimated mortality rate of 30-60% and patients require urgent surgical management to relieve the underling cause [4].…”
Section: Discussionmentioning
confidence: 99%
“…[4] Where gastric carcinoma was the indication for the initial operation, [5] tumour recurrence was noted to outweigh other usual causes such as adhesions, anastomotic ulcers, stenoses, internal hernias in surgically created foraminae (including in the mesentery), twisting foci, or intussusceptions. [2,6] …”
Section: Frequency and Causesmentioning
confidence: 99%